Influence Annealing Temperature of Working Electrode and Scattering Layer to Efficiency of Dye-Sensitized Solar Cell (DSSC) - Mar Atun Shofwati; Fahru Nurosyid; Yofentina Iriani (Lambung Mangkurat University Press, 2019)
DSSC was kind of solar cell based on dye as sensitizer or photon absorber. Scattering layer method used to optimize photon scattered process on working electrode. In this research, variation temperature annealing of scattering layer have done to find out the effect toward DSSC’s efficiency. TiO2 nanopowder and TiO2 transparent are used as semiconductor layer and scattering layer, respectively which deposited with spin coating method. Platinum was deposited on counter electrode with brush painting method. TiO2 nanopowder was annealed at 400oC, while scattering layer were annealed at variation temperature i.e. 400oC, 450oC, 500oC, and 550oC. Dye Ruthenium Complex N719 was used as sensitizer on DSSC’s structure. Result of XRD characterization on working electrode show that highest crystallite size is 18.92 nm with annealing process of scattering layer at 450oC and decreased when the temperature is over 400oC. Photovoltaic characterization used Keithley I-V meter. The annealing process of scattering layer at temperature 450oC has good photovoltaic parameter. This cell has short circuit current (Isc) is A, open circuit voltage (Voc) is 0.39 V, and fill factor is 0.51. The value of Voc was influenced by the absorption of dye in TiO2 layer. Annealing scattering layer at 450oC produce crystallite structure with higher TiO2 surface area, it can optimize photon absorption of dye more than the annealing process over 450oC. Scattering layer which annealing at 450oC can increase efficiency of DSSC cells from % to %.